Rehydration characteristics and kinetics of traditionally dried mussels at different temperatures - Ozyalcin, Zehra Ozden; Kipcak, Azmi Seyhun (YILDIZ TECHNICAL UNIV, 2023)
The rehydration kinetics is an important element in both the manufacture and consumption of dry goods. The rehydration behavior and effective diffusion coefficients of blue mussels (Mytilus edulis) dried with traditional methods were investigated in this study at various drying and rehydration temperatures, as well as under vacuum and non-vacuum environments. The drying temperatures in the early study were between 60 and 80 & DEG;C, whereas the rehydration temperatures were between 20 and 40 & DEG;C. The maximum rehydration rates for mussels were calculated between 0.0094 -0.0022 g/gxmin for the oven drying and between 0.0127 -0.0070 g/gxmin for vacuum oven drying. Vacuum application has been seen to boost the rehydration rate and rehydration ratio by shortening the time it takes to reach rehydration saturation. The compatibility of the obtained rehydration data with the Peleg, Two-Term and Weibull mathematical models was examined and a higher agreement was reached with the Two-Term model for almost all experimental sets.
Keywords: Blue Mussel; Rehydration Ratio; Seafood; DRYING CHARACTERISTICS; MICROWAVE; Engineering